PEMENUHAN KEBUTUHAN ISTIRAHAT DAN TIDUR PADA ANAK: LITERATURE REVIEW - Ni Ketut Apriliani Devi; Mochamad Heri (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Children are a gift from the almighty God that must be guarded, educated as resources, children are invaluable wealth. Each individual needs a different amount of rest and sleep. Physical and emotional health depend on the ability to meet basic human needs. The purpose of this literature review is to identify and analyze journals related to the topic / title of discussion, namely to explain efforts to meet the needs of rest and sleep in children. The method used is literature review with PICO analysis based on evidence-based practice by analyzing 10 journal articles (8 national journals and 2 international journals). The literature criteria used are the publication of articles from the last 3 years from 2017 to 2020, and articles that can be accessed free full text on Google Scholar and PubMed. The discussion in this study can help readers and nurses understand that meeting the basic needs of rest and sleep in children is very important to be given because it can provide stimulation / positive impact in improving the health status of children.